219 Have New National Guidelines Changed Practice in Referrals with Suspected Ureteric Colic?. (12th October 2021) - Boyle, C; Young, J
Abstract: Aim: To assess how many patients had a non-contrast CT as first-line investigation for suspected renal colic, and how this was affected by the release of the 2019 NICE guidelines. A secondary aim was to assess the proportion of patients who had CT KUBs that demonstrated a ureteric calculus. Method: CT KUB scans performed over two separate 3 month periods were identified. These reflected periods of time before and after the new NICE guidelines. Electronic records were used to assess if the patients had an ultrasound performed as the initial diagnostic investigation, instead of a CT scan. The results of the scans were reviewed to identify if a ureteric or renal calculus had been positively identified. Results: In the period before the new guidelines, 61 patients were scanned. 4 had an ultrasound to assess for a stone prior to a CT. All of these patients were medical inpatients. None of the ultrasounds diagnosed a stone. 22/61 patients had CT-proven stones (36%) In the period after the new guidelines, 79 patients were scanned. 12 had an ultrasound to assess for a stone prior to a CT. 8 were medical patients, 3 were surgical and 1 was gynaecological. 1 ultrasound diagnosed a stone. 28/79 patients had CT-proven stones (35.4%) Conclusions: The release of new guidelines did not improved compliance with suggested imaging pathways. This clearly demonstrates an area for improvement. It is also worth noting that only 1/3 of referrals with suspected renal colic did actually have a stone, which has implications for specialty referral pathways.